The house, the world, and the theatre : self-fashioning and authorial spaces in the prefaces of Hawthorne, Dickens, and James - Cáffaro, Geraldo Magela (Cambridge Scholars Publishing, 2016)
The House, the World, and the Theatre departs from three ideologically resonant spatial metaphors to explore key aspects of nineteenth-century literature and culture. At the centre of the discussion is the way authors fashioned themselves to cater to ever-expanding audiences and to the new conditions of publishing. The prefaces of Hawthorne, Dickens, and James illustrate the conflicts underlying the new forms of self-definition in the nineteenth century and mediate the perception of authorship as a category that blurs the boundaries between social life and performance. This book combines genre.